An Unusual Case of Breast Implant-Associated Anaplastic Large Cell Lymphoma. (9th June 2022) - Premji, Sarah; Barbieri, Andreia; Roth, Christine; Rohren, Eric M.; Rivero, Gustavo; Teegavarapu, Sravanti P
Abstract : Introduction . Breast implant-associated anaplastic large cell lymphoma (BIA-ALCL) is a rare disease entity associated with textured breast implants. Though the clinical course is typically indolent, BIA-ALCL can occasionally invade through the capsule into the breast parenchyma with spread to the regional lymph nodes and beyond including chest wall invasive disease. Case . We present the case of a 51-year-old female with a history of bilateral silicone breast implants placed approximately twenty years ago who presented with two months of progressively enlarging right breast mass. Ultrasound-guided biopsy of right breast mass and right axillary lymph node showed CD 30-positive ALK -negative anaplastic large cell lymphoma, and staging work up showed extension of the tumor to chest wall and ribs consistent with advanced disease. She received CHP-BV (cyclophosphamide, doxorubicin, prednisone, and brentuximab vedotin) for six cycles with complete metabolic response. This was followed by extensive surgical extirpation and reconstruction, radiation for residual disease and consolidation with autologous stem cell transplant. She is currently on maintenance brentuximab vedotin with no evidence of active disease post autologous stem cell transplant. Conclusion . Treatment guidelines for advanced chest wall invasive BIA-ALCL are not well defined. Lack of predictive factors warrants mutation analysis and genetic sequencing to identify those at highest risk of progression to chest wall invasive disease. This rare case highlights the need for definitive consensus on the optimal management of chest wall invasive BIA-ALCL.